2023
DOI: 10.3389/fneur.2023.1150477
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between respiratory and oromotor events differ between motor phenotypes in patients with obstructive sleep apnea

Abstract: PurposeThe present study investigated the relationship between sleep bruxism (SB) and obstructive sleep apnea (OSA) in relation to the sleep architecture.MethodsWe conducted a cross-sectional study. Polysomnographic recordings were performed on 36 patients. Sleep, respiratory, and oromotor variables, such as rhythmic masticatory muscle activity (RMMA) and non-specific masticatory muscle activity (NSMA), were compared between OSA patients with or without SB. A correlation analysis of the frequency of respirator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 45 publications
1
1
0
2
Order By: Relevance
“…Previous studies have proposed different pathogenesis for tonic events compared with phasic and mixed events, as well as a relationship between the TERT gene polymorphism and phasic events but not tonic events (Macek et al, 2022). The positive correlation between hypoxia and phasic events, but not tonic events, supports the hypothesis that phasic and tonic types of bruxism exhibit distinct features and roles (Michalek-Zrabkowska, Wieckiewicz, Haraki et al, 2023;Okura et al, 2023). Recently, Toyota et al (2022) demonstrated a significantly higher frequency of RMMA and percentage of arousals with RMMA in subjects with sleep bruxism compared with controls, with no significant differences observed for nonrhythmic promotor events.…”
Section: The Effect Of Clusters On Polysomnography Parameterssupporting
confidence: 52%
“…Previous studies have proposed different pathogenesis for tonic events compared with phasic and mixed events, as well as a relationship between the TERT gene polymorphism and phasic events but not tonic events (Macek et al, 2022). The positive correlation between hypoxia and phasic events, but not tonic events, supports the hypothesis that phasic and tonic types of bruxism exhibit distinct features and roles (Michalek-Zrabkowska, Wieckiewicz, Haraki et al, 2023;Okura et al, 2023). Recently, Toyota et al (2022) demonstrated a significantly higher frequency of RMMA and percentage of arousals with RMMA in subjects with sleep bruxism compared with controls, with no significant differences observed for nonrhythmic promotor events.…”
Section: The Effect Of Clusters On Polysomnography Parameterssupporting
confidence: 52%
“…Another study, conducted by Saito, found a positive and significant correlation between OMA and AHI [24]. As Kato pointed out in 1999, the OMA activity may introduce a bias if it is not excluded from the neurophysiological analyses [62].…”
Section: Discussionmentioning
confidence: 95%
“…Por fim, Okura, et al, 2023 sugerem que pacientes que apresentam tanto AOS quanto BS possuem um fenótipo fisiológico único de AOS. Esses achados apoiam descobertas anteriores que indicam que os eventos respiratórios durante o sono não são um gatilho direto para RMMA.…”
Section: Relação Entre Apneia Obstrutiva Do Sono E Bruxismo Do Sonounclassified
“…A maioria dos eventos de apneia central ocorreu após o episódio de BS; pacientes com apneia grave apresentam tendência a ter índices de bruxismo mais elevados quando comparados a pacientes com apneia leve e moderada. Okura, et al, (2023) Relationships between respiratory and oromotor events differ between motor phenotypes in patients with obstructive sleep apnea.…”
Section: Kazubowska-unclassified